Aquatic gymnastics program to improve kinesthetic manual praxis in children with Down syndrome - Diyana Georgieva; Veselina Ivanova (IP Iermakov S.S., 2023)
Background and Study Aim. An alternative solution to improve the praxis function in children with Down syndrom is the application of modern therapeutic programs that take place in the aquatic environment. The article focuses on a study tracking the effects of a therapeutic program based on water gymnastics resources as an alternative technology to improve kinesthetic manual praxis in individuals with Down syndrome. Material and Methods.  Thirty children with Down syndrome (aged between 9 and 11 years) participated in the experiment and were differentiated in equal numbers into two groups: experimental (undergoing an 11-month therapeutic water gymnastics course) and control (taught using traditional technologies). The research battery for tracking the dynamics in the kinesthetic organization of manual movements included three neuropsychological probes with six items each, performed separately by the fingers of both hands. The empirical data were processed according to generally accepted methods of mathematical statistics: a Shapiro-Wilk test for the assumption of normality, descriptive statistics for the dependent variables and an independent samples t- test to verify between-group differences. SPSS 16.0 statistical package was used for statistical analysis, with a level of significance α = 0.05. Results. In the primary phase, the two groups were homogeneous in terms of the initial results of their performance in the area of fine motor movements. In the final phase, a statistically significant difference was identified between the experimental and control groups in the performance of all three probes: Reproduction of finger postures by the visual model (t = 4.053, p<0.001); Reproduction of finger postures by the kinesthetic model (t = 2.973, p<0.01); Transfer of finger postures by the kinesthetic model (t = 2.866, p<0.05). A significant improvement was registered in the experimental group's performance in all components of manual praxis (Δ= 15.70%; Δ= 12.58%;  Δ= 10.39%). Conclusions. The positive dynamics in praxis function development within the studied domain serve as clear evidence. These changes in the realization of purposeful, pre-planned manual actions can be generated through a well-structured training and therapy program utilizing the benefits of water gymnastics as an intervention method. This is a sufficiently encouraging fact for children with Down syndrome, given the specific psychomotor profile determined by the genetic pathology.